Analisis Kejadian Missfile Berkas Rekam Medis Rawat Jalan di Puskesmas Bangsalsari - Try Ganjar Wati; Novita Nuraini (Politeknik Negeri Jember, 2019)
Based on preliminary research at Bangsalsari Public Health Center were found that on December 2018 to March 2019 for 53 out of 200 medical record files were misplaced or misfiling. The misplaced file or misfiling could inhibit and led into delay on the patient service process. In addition, a new file would be created to replace the missing medical record file and affected the unsustainable medical record files. The aim of this research was to analyze, determine the priority causes and to fix the problem of misfiling incident using USG (Urgency, Seriousness, Growth) and brainstorming in Bangsalsari Public Health Center. This research is qualitative research and collecting the data using interview, observations, documentation, questionnaire, and brainstorming. The result of this research were the priority causes of mis filing incident coming from the broken folders and stacking files which had no folders. The improvement efforts for the problem are made by replacing the broken folders, duplicating medical record folders, gradually providing folders on medical record files, adding some filing cabinets to avoid stacking files, and separating inactive files.